Optimal Portfolio Analysis Using the Single Index Model - Ari Gunawan; Erlina Pakki; Fauzi R Rahim (Hasanuddin Journal of Business Strategy, 2021)
This study aims to determine the formation of the optimal portfolio using the single-index model and find out whether there are differences between the optimal portfolio and the non-optimal portfolio of stock. Further, it also finds out the percentage of the proportion of funds and the expected returns and risks for each stock making up the optimal portfolio before the Covid-19 period from February 2019 to January 2020 and during the Covid-19 period from February 2020 to January 2021). The study applied a descriptive quantitative approach. Of 45 stocks listed in the LQ45 Index, the study takes as many as 28 stocks as samples, which is then analyzed using Single Index Model. We found that there are three stocks making up the optimal portfolio before the Covid-19 period. Those stocks are Media Nusantara Citra Tbk (MNCN) with the proportion of funds 18.55%, Bank Central Asia Tbk (BBCA) with 69.83%, and Bank Rakyat Indonesia (Persero) Tbk (BBRI) with 11.63%. The expected return of this stock group is 0.023669025 or 2.37% and it's a portfolio risk of 0.000721873 or 0.07%. Meanwhile, during the Covid-19 period, there were four stocks that formed the optimal portfolio, namely Aneka Tambang Tbk (ANTM) shares with the fund proportion of 38.41%, Indah Kiat Pulp & Paper Tbk (INKP) with 27.30%, Bukit Asam Tbk (PTBA) with 25.18%, and United Tractors Tbk (UNTR)with 9.11%. The expected return is 0.078544263 or 7.85% with a portfolio risk of 0.012364093 or 1.24%.